Flow structure effects on turbulent transport using computations - Pham, Le Kieu Oanh (My University, 2023)
Turbulent flow is the most typical flow in various fields such as biological, chemical and industrial applications and atmospheric phenomena. The main goal of this research is to investigate the fundamental effects of the very large-scale structures of turbulence on convective transport and the effects of the interplay between molecular diffusion and flow structure on turbulent transport. Applying Lagrangian computations in conjunction with direct numerical simulations for turbulent flow in channel and Couette flow, it could explore the effects of the very large-scale turbulent fluid motions on scalar transport and determine the mechanism by which they contribute to transport. From that we can develop a predictive model for turbulent scalar transfer and control this. One of our applications is the effect of turbulent flow in cardiovascular devices such as blood pumps, ventricular assist devices (VADs) and even heart valves. According to clinical findings, VAD patients often suffer from acquired von Willebrand disease after VAD implantation. Indeed, the von Willebrand Factor protein is susceptible to supraphysiological shear stress and extensional stress which leads to the conformational change of vWF. Apart from that, the detailed measurement of stresses in a hemodynamic velocity field is difficult, especially in-situ for turbulent flow conditions. In such cases, the use of computational methods has become critical for both the probing of the hemodynamic conditions and for device design. Therefore, recognizing advantages of Direct Numerical Simulation (DNS) and Lagrangian Scalar Tracking (LST) we applied it to the case of vascular assist devices and indicate (i) the development of a numerical methodology for obtaining the history of the stresses on vWF molecules as they move in a flow field; (ii) the detailed calculation of shear and extensional stress statistical distributions on the vWF molecules showcasing the importance of the tails of the distributions in addition to average values; and (iii) the investigation of the importance of the flow field configuration and of the location of vWF injection on the distribution of stresses over time. This study’s contribution is the statistical data for hydrodynamic stress on vWF along the trajectories of protein particles that could contribute to design the medical devices and reduce the cost of experiments. The second application is to investigate the role of helicity in turbulent transport in channel and Couette flow and the interplay between helicity with scalar transport and coherent structures. Helicity is also important for understanding the relationship between coherent structures and turbulent kinetic energy. There has been a hypothesis that coherent structures at different scales are associated with regions in which helicity is large and dissipation of turbulent kinetic energy is low. Low dissipation means that these coherent structures could survive for a long time leading to significant impacts on the flow. In this study, Direct Numerical Simulation (DNS) of turbulent Poiseuille and Couette flow were used in combination with Lagrangian Scalar Tracking (LST) at various Schmidt numbers of 0.7, 6 and infinite (i.e., fluid particles), and the friction Reynolds number for both simulations was 300 to probe the correlation between helicity and dissipation, and the role of helicity in the regions of coherent structures in anisotropic turbulence. Our Lagrangian Scalar Tracking could provide the fluid velocity at each marker location with time. From these data, one can compute turbulent kinetic energy dissipation, vorticity, and helicity along these trajectories. The autocorrelation coefficients, the cross-correlation coefficients and the joint probability density function are employed to investigate the relation between helicity and dissipation, and helicity and vorticity and with the vertical velocity in the Lagrangian framework. In addition, conditional statistics for scalar markers are evaluated in flow regions of high dissipation or coherent structure regions based on vortex identification criteria. In addition, scalar markers that dispersed most or least in the flow field were also calculated to provide more evidence for the role of helicity in transport in turbulent flow.
Keywords: Turbulent flow; Transport; Computation